(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрены существующие подходы к оценке внешнего водообмена искусственных водоемов. На примере Камского и Воткинского водохранилищ показаны их положительные моменты, применимость к характеристике обмена вод. PARAMETERS OF EXTERNAL WATER EXCHANGE OF ARTIFICIAL RESERVOIRS The parameter of external water exchange offered by L.I.Dubrovinym, reflects character of regulation of a drain water reservoirs. A parameter of an exchange of waters, the presented by S.V.Grigorevym, reflects a natural component of nature-technogenic system, what the water reservoir is. It is most brightly expressed for the uppermost reservoirs in the cascade. Concerning the water reservoirs which are being cascade position, the given parameter reflects both parties of nature-technogenic system. Researches on Каma and Votkinsk water reservoirs for the long-term period have proved first two positions.